Polish Chambers of Commerce towards Problems of Sustainable Development - Daria ZAWALSKA (Communications of International Proceedings, 2021)
The paper provides broad review of the available sources on the way sustainable development issue is being raised by selected polish chambers of commerce. The review reveals that only few of the chosen organizations pay attention to the problem of sustainable development or green economy and that these activities are limited to single, uncoordinated actions. However, it is worth noting that the majority of researched institutions declares the will of acting in this respect. These themes could serve as important staring point of further study of the way the chambers act on behalf of sustainable development.
Keywords: Sustainable development; green entrepreneurship; green business; chambers of commerce